Large-scale preparation of Co nanoparticles as an additive in carbon fiber for microwave absorption enhancement in C band - Y. X. Zhu (Nature Portfolio, 2021)
Abstract Recent studies have found that the core–shell structured metal nanoparticles and porous carbon nanofibers (PCNF) are combined into a microwave absorbing material through electrospinning, which exhibits excellent microwave absorption performance. In this study, the core–shell structure Co nanoparticles prepared by the self-developed HEIBE process (production rate of > 50 g/h) were combined with porous carbon fibers, and their absorbing properties were greatly improved. The morphology of Co/PCNF demonstrated that CoNPs are randomly dispersed in the porous carbon nanofibers and carbon nanofiber form complex conductive network which enhances the dielectric loss of the materials. Meanwhile, the Co/PCNF has a low graphitization and shows a significant improvement in permittivity due to the combination of CoNPs and high conductivity of carbon material. The maximum reflection loss (RL) of Co/PCNF reaches − 63.69 dB at 5.28 GHz with a thickness of 5.21 mm and the absorption bandwidth (RL ≤  − 10.0 dB) is 12.92 GHz. In terms of 5.60 mm and 6.61 mm absorber, there are two absorption peaks of − 47.64 dB and − 48.30 dB appear around 12.50 GHz and 14.10 GHz, respectively. The results presented in this paper may pave a way for promising applications of lightweight and high-efficiency microwave absorbing materials (MAMs).